2021
DOI: 10.1101/2021.02.08.430186
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular evolutionary dynamics of energy limited microorganisms

Abstract: Microorganisms have the unique ability to survive extended periods of time in environments with extremely low levels of exploitable energy. To determine the extent that energy limitation affects microbial evolution, we examined the molecular evolutionary dynamics of a phylogenetically diverse set of taxa over the course of 1,000-days. We found that periodic exposure to energy limitation affected the rate of molecular evolution, the accumulation of genetic diversity, and the rate of extinction. We then determin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Despite the inability to form protective structures, all replicate populations of Δ spo0A from all transfer regimes survived the experiment. This pattern of consistent survival is a marked difference from a previous experiment that used an identical energy-limitation design, where bacterial taxa from diverse phyla (Bacteroidetes, Proteobacteria, and Deinococcus-Thermus) frequently went extinct in 10 and 100-day transfer regimes [31]. This comparison suggests that Bacillus is exceptionally capable of surviving and evolving in harsh environments, even without access to what is generally considered its primary survival strategy.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…Despite the inability to form protective structures, all replicate populations of Δ spo0A from all transfer regimes survived the experiment. This pattern of consistent survival is a marked difference from a previous experiment that used an identical energy-limitation design, where bacterial taxa from diverse phyla (Bacteroidetes, Proteobacteria, and Deinococcus-Thermus) frequently went extinct in 10 and 100-day transfer regimes [31]. This comparison suggests that Bacillus is exceptionally capable of surviving and evolving in harsh environments, even without access to what is generally considered its primary survival strategy.…”
Section: Resultsmentioning
confidence: 68%
“…Populations were regularly plated to test for contamination. An identical experiment was concurrently run with the WT strain, which was previously described [31].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rise of evolve-and-resequence experiments as high-throughput screens for adaptation 4 has allowed researchers to identify recurrent mutations across replicate populations 4,5 , paring down the vast number of potentially adaptive mutations into those that putatively confer the largest fitness benefits. Furthermore, evolveand-resequence experiments have revealed that the outcomes of evolution are often conditional on the ancestral genotype of a microbial population [6][7][8][9][10] or the environment in which it was maintained [11][12][13][14][15] , a phenomenon known as divergent evolution.…”
Section: Observationmentioning
confidence: 99%